Connections between upwelling patterns and phytoplankton variability under different coastal regimes in SW Iberia Peninsula - Krug, Lilian (2012)
The region off southwestern Iberia (NE Atlantic) encompasses a wide variety of oceanographic regimes, including differently (geographic) oriented coastal areas impacted by upwelling, riverine inputs and submarine groundwater discharge, submarine canyons and seamounts, and open ocean waters, thereby potentially promoting zone-specific phytoplankton dynamics. Overall, this heterogeneous region is classified as being very sensitive to climate change, and climate-driven alterations (e.g., sea surface warming, changes in upwelling patterns and intensity) have been recently reported for the area. The present study aims to understand the contribution of upwelling to seasonal and interannual variability of coastal phytoplankton, using a remote sensing-based approach. Phytoplankton variability was evaluated using satellite-derived chlorophyll-a (Chl-a), as a proxy for phytoplankton biomass, and primary productivity (PP). Chl-a were obtained from merged SeaWiFS (Seaviewing Wide Field-of-view Sensor), MeRIS (Medium Resolution Imaging Spectrometer) and MODIS-Aqua (Moderate-resolution Imaging Spectroradiometer) sensors at Globcolour portal. PP data at 9.25 km resolution were derived from Eppley’s Vertically Generalized Production Model, based on SeaWiFS and MODIS-Aqua and available at the Ocean Productivity site. Upwelling intensity was estimated using the difference in sea surface temperature (SST) between off and nearshore zones. Advanced Very-High Resolution Radiometer (AVHRR) 4 km SST were obtained from Pathfinder database. Other phytoplankton environmental drivers, such as local (e.g., river flow) and global (e.g., North Atlantic Oscillation - NAO) climate variables, were also analysed. The study area was divided into subareas differently impacted by upwelling and riverine flow, and satellitederived data was averaged for each zone. Seasonal and interannual variability covering a 14-year time series (1998- 2011) for each variable/region were explored. Chl-a at offshelf locations was significantly lower than coastal areas, and exhibited a fairly stable unimodal annual cycle, with maximum during March. Coastal locations displayed more variable annual patterns, with spring and summer Chl-a maxima, reflecting the impact of upwelling events and freshwater inputs. In respect to interannual variability, NAO index and coastal Chl-a were negative and significantly correlated, with 1-month lag. Chl-a interannual trends were also correlated to local climate variables, namely riverine flow for the easternmost coastal zone. The correlation between upwelling intensity and phytoplankton off SW Iberia is region-dependent being less strong within regions dominated by riverine influence.